Effect of probiotic lactobacilli on protein hydrolysis, volatilomics, texture and sensory properties of buffalo yogurt: A comparative study - Karagol, Mehmet Akif; Tarakci, Zekai; Tekin, Ali; Hayaloglu, Ali Adnan (Elsevier Sci Ltd, 2026)
This study investigated the effects of different probiotic lactobacilli (Lacticaseibacillus paracasei ATCC 334, Lactobacillus helveticus ATCC 15009 and Lactiplantibacillus plantarum ATCC 14917, on the physicochemical, microbiological, biochemical, textural, volatile and sensory properties of buffalo yogurt during a 21-day storage period. Yogurts produced with probiotic strains showed higher proteolysis (up to 8.12 %) and higher gamma-aminobutyric acid (GABA) content (up to 19.75 mg/100 g) compared to traditional (Karamaya, KM) and commercial (YC-350) cultures. A total of 65 volatile compounds were identified. The probiotic-containing samples hade higher levels of acids and alcohols, while the non-probiotic samples were richer in ketones. Peptide profiling revealed characteristic patterns for each culture type, particularly for L. plantarum and L. helveticus. This was consistent with a higher degree of hydrolysis in probiotic yogurts. Antioxidant activity varied by culture and storage time, with probiotic samples showing different trends in DPPH and ABTS assays. Microbiological counts confirmed increased viability of lactobacilli in probiotic yogurts, reaching 9.06 log CFU/g. In contrast, KM samples had higher yeast and mold counts due to their diverse natural microflora. Texture analysis showed increased firmness and shear work during storage, with L. paracasei having the highest firmness. Sensory evaluation revealed that KM and YC yogurts were preferred in terms of taste and overall acceptability In contrast probiotic samples deviated from the known flavour profile, despite their functional benefits. Overall, these results highlight the potential of probiotic cultures to enhance the functional value of buffalo yogurt, while emphasizing the need to optimize starter combinations to align health-promoting properties with consumer sensory preferences.
Keywords: Yogurt; Buffalo milk; Antioxidant activity; TPA; Volatiles; Lactobacillus spp.; Free amino acids; Karamaya